1965
DOI: 10.1002/app.1965.070090820
|View full text |Cite
|
Sign up to set email alerts
|

Effects of thermal exposure on the physicochemical properties of polyamides

Abstract: Nylon 66 and nylon 6 yarns were exposed in air, nitrogen, and vacuum to temperatures from 136 to 215OC. for periods from 5 min. to 17.5 hr. The moisture absorption of both fibers is reduced by the exposure independently of the presence of oxygen or of antioxidant. This is ascribed to secondary crystallization. Siultaneuusly, the electrical resistivity is increased. The breaking strength is reduced by exposure in the presence of oxygen anlesa the polymer contains antioxidant. The extent of oxidative cleavage wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

1976
1976
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…This study was performed at 200°C on unfilled nylon for time periods up to 36 h in a nitrogen or an oxygen atmosphere. Their findings and others (2)(3)(4) have provided various reaction mechanisms for the degradation of nylon.…”
Section: Introductionmentioning
confidence: 93%
“…This study was performed at 200°C on unfilled nylon for time periods up to 36 h in a nitrogen or an oxygen atmosphere. Their findings and others (2)(3)(4) have provided various reaction mechanisms for the degradation of nylon.…”
Section: Introductionmentioning
confidence: 93%
“…The increase of tensile strength and modulus flexural property during reprocessing can be explained by an increase of molecular weight. 9,10 The gel permeation chromatography (GPC) technique was used to obtain the change in average molecular weight (M w and M n ) of the nylon-6 virgin with respect to the reprocessed material. The results of the M w and M n are shown in Figures 6 and 7, respectively.…”
Section: Characterization and Mechanical Testingmentioning
confidence: 99%
“…Thus, it is important to investigate the interaction between simultaneously in the interior. Valko and Chiklis 10 showed that the molecular weight deprocess-induced degradation and the magnitude of degradation during subsequent service. Figure creases on heating in the presence of air but increases on heating in the presence of antioxidants 1 is a schematic illustration of process-induced and service-induced degradation on the individual or in a nitrogen atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10] The literature (4-10) addresses changes in calorimetric behavior, 4,5 infrared (IR) absorption bands, [6][7][8] and mechanical properties. [8][9][10] It is also known that the surface region of a thermally aged polyamide material will undergo more severe degra- Figure 1 Schematic illustration of process-induced dation than the interior. 9,11 Molecular weight deand service-induced degradation of the individual termination 9,11 showed that the molecular weight phases of glass-fiber-reinforced thermoplastics.…”
Section: Introductionmentioning
confidence: 99%